Bacteriological and Molecular Study of Fluoroquinolones Resistance in Pseudomonas aeruginosa Isolated From Different Clinical Sources - Al-Mayali, Mustafa Abd; Salman, Ehab D. (Iraqi Journal of Science, 2020)
The present study was conducted to investigate the resistance of fluoroquinolones (FQs) and the effects of mutations in the resistance gene in clinical isolates of P. aeruginosa isolated from different sources in Al-Hussein Hospital, Al-Samawah city, Iraq. The basic mechanism of the resistant of fluoroquinolones in P. aeruginosa is via mutations occurring in the basic bacterial gyrA gene encoding-subunit A of DNA gyrase . Forty clinical isolates from various sourced (burn 7 (17.5 %), wound 7 (17.5 %), ear 2 (5 %), operation room 12 (30 %), urine 3 (7.5 %), and industrial dialysis center 9 (22.5 %)) were isolated based on bacteriological methods confirmed by 16s rRNA gene using PCR technique. A sensitivity test was conducted to all isolates by Kirby-Pour method using 7 antibiotics of fluoroquinolones. Amongst the 40 clinical isolates, 10 were resistant and 3 were sensitive to all tested antibiotics, while 27 were intermediate, resistant and sensitive to two or more of tested antibiotics, with the resistance being confirmed by the minimum inhibitor concentration (MIC) test. The ten resistant isolates were used to examine the mutations in gyrA gene. A direct sequence method was used and revealed eight mutations in gyrA gene at different positions. In addition, we found that fluoroquinolone activity in the sensitive isolates, after sequencing for these isolates, is a bacteriostatic activity. The results of this study showed the gyrA mutations resulting from the excessive use of antibiotics are one of the mechanisms may be that leading to fluoroquinolone resistance.